Decarbonising meat: exploring greenhouse gas emissions in the meat sector. (September 2017) - aan den Toorn, S.I.; van den Broek, M.A.; Worrell, E.
Abstract: Consumption of meat is an important source of global greenhouse gas (GHG) emission and deep decarbonisation of the whole meat production chain is required to be able to meet global climate change (CC) mitigation goals. Emissions happen in different stages of meat production ranging from agricultural input production, feed production, livestock production to slaughtering, meat processing, and retail. An overview of direct emissions from processes in the meat sector themselves and indirect emissions from energy consumptions would provide a clearer picture for potential CC impact reduction. This paper explores the total GHG emissions and data availability within the meat sector of the pig, chicken, and cattle meat product system. Through statistical data provided by FAOSTAT and supplementary data from literature, the CC impacts of energy use and process GHG emissions in the pig, chicken and cattle meat life cycle are estimated. Cattle dominates, but pig and chicken meat have a sizable amount of GHG emissions with a relatively high contribution from agricultural inputs and post-farm processes. However, uncertainty and unavailability of data are large for the energy consumption, direct GHG emissions, and product flows of post-farm and agricultural input processes. In order to gain a more complete understanding of the total CC impacts of the meat sector, further research is necessary to reduce the uncertainty in the considered life cycle stages and to quantify the processes and meat products that have been excluded from this study.